Analysis of the literacy level of health workers regarding Islamic life insurance at the Ofa Padang Mahondang Community Health Center - Cahya Purwati Sinulingga; Andri Soemitra; Nuri Aslami (Journal of Islamic Economics Lariba, 2023)
IntroductionFinancial literacy on Islamic life insurance is considered low. Various things can be the causes of this low literacy including the lack of socialization, education, and professional collaboration programs.ObjectivesThis study aims to analyze the literacy level of health workers regarding Islamic life insurance considering the phenomenon of still very low penetration and density of such product. MethodThis research uses descriptive quantitative methods. Primary data was obtained through a questionnaire. The population of this study was 38 health workers who worked at the Ofa Padang Mahondang Village Health Center, Pulau Rakyat District, Asahan Regency, North Sumatra Province.Results57.9% of respondents had a high level of financial literacy, being able to answer correctly above 80%. 34.2% of respondents were in the middle category, being able to answer correctly between 60%-80%. Only 7.9% respondents were in low category, being able to answer correctly below 60%. ImplicationsThe study highlights the importance of continuous education and awareness campaigns about Islamic insurance among healthcare professionals and the broader population.Originality/NoveltyThis study contributes to efforts to increase knowledge about Islamic life insurance for health workers as the spearhead of health services in Indonesia.